1997
DOI: 10.1111/j.1600-051x.1997.tb00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease related to diabetic status

Abstract: Variation in the periodontal health status and the response to oral hygiene education, scaling and root planing were studied in 36 subjects with type-1 diabetes mellitus (DM) and in 10 non-diabetic control subjects. The age range of the subjects was 24-36 years. The diabetic group was divided into 3 subgroups based on the levels of glycosylated hemoglobin (HbAlc) over a 3 year period and the presence of diabetic complications as follows: (D1) subjects with good metabolic control and no complications (n=13), (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
0
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 26 publications
10
105
0
8
Order By: Relevance
“…to that of non-diabetics 23) . On the other hand, it was reported that poorly controlled diabetics respond less successfully to periodontal therapy relative to well-controlled and non-diabetics 19) . Tervonen and Karjalainen 19) reported that although poorly controlled diabetics responded to nonsurgical therapy similarly to controls in the short term (4 weeks), in the absence of maintenance therapy, more rapid recurrence of periodontal pockets and subgingival calculus was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to that of non-diabetics 23) . On the other hand, it was reported that poorly controlled diabetics respond less successfully to periodontal therapy relative to well-controlled and non-diabetics 19) . Tervonen and Karjalainen 19) reported that although poorly controlled diabetics responded to nonsurgical therapy similarly to controls in the short term (4 weeks), in the absence of maintenance therapy, more rapid recurrence of periodontal pockets and subgingival calculus was found.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was reported that poorly controlled diabetics respond less successfully to periodontal therapy relative to well-controlled and non-diabetics 19) . Tervonen and Karjalainen 19) reported that although poorly controlled diabetics responded to nonsurgical therapy similarly to controls in the short term (4 weeks), in the absence of maintenance therapy, more rapid recurrence of periodontal pockets and subgingival calculus was found. The data from the present study, however, seem to indicate that careful control of disease in patients with diabetes will result in a similar low frequency of recurrent periodontitis to that seen in non-diabetic patients if they receive treatment for periodontal disease and follow a careful plaque control program.…”
Section: Discussionmentioning
confidence: 99%
“…The short and long term response to periodontal therapy in well controlled diabetics with regular maintenance therapy is as good as non-diabetic patients [23]. However, long-term response to nonsurgical periodontal therapy in a poorly controlled diabetic patient would result in rapid recurrence of the original deep pockets [24]. Hence, by maintaining good oral hygiene and keeping blood sugar level in check, failure of nonsurgical periodontal therapy can be prevented.…”
Section: Glycemic Controlmentioning
confidence: 99%
“…87 Other longitudinal studies demonstrate these concepts; poorly controlled diabetics do not respond to periodontal therapy as well as controlled diabetics or non-diabetics. 88,89 Genetic factors play an important role in susceptibility to periodontal disease [90][91][92] as well as to systemic diseases. The impact of a poorly regulated immune response in fuelling the progression of periodontal destruction secondary to bacterial plaque is well documented.…”
Section: An Overview Of Periodontitis and Dmmentioning
confidence: 99%